Reschedule the Shunting and Service Scheduling Plan After Disturbances at a Chinese High-Speed Railway Depot - Jintang Shi; Haodong Li; Daoqi Wang; Pieter Vansteenwegen (IEEE Access, 2024)
Electrical Multiple Units (EMUs) need to undergo services like repairing, cleaning and wheel turning according to a train shunting and service scheduling (SSS) plan at the high-speed railway depot. Disturbances in the timetable at the station and overtime services affect the original SSS plan. Therefore, frequent modifications to the original SSS plan and rescheduling of some EMUs are required to recover the feasibility of the plan. This paper considers a rescheduling method for integrating train shunting, service scheduling and routing at EMU depots with various layouts. In this paper, the movement process of EMUs at depots is represented with the help of a two-layer time-space network. A heuristic algorithm for rescheduling is designed. Case studies based on a real-world depot show that the heuristic can repair the original SSS plan in 180 seconds while ensuring that the new SSS plan is as close as possible to the original SSS plan.